2005
DOI: 10.4064/cm102-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Nonmeasurable algebraic sums of sets of reals

Abstract: Abstract. We present a theorem which generalizes some known theorems on the existence of nonmeasurable (in various senses) sets of the form X+Y . Some additional related questions concerning measure, category and the algebra of Borel sets are also studied.Sierpiński showed in [14] that there exist two sets X, Y ⊆ R of Lebesgue measure zero such that their algebraic sum, i.e. the set X + Y = {x + y : x ∈ X, y ∈ Y } is nonmeasurable. The analogous result is also true for the Baire property.Sierpiński's construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…It is easy to check (see similar arguments in [5]) that every Bernstein set is completely nonmeasurable with respect to every σ -ideal with a base consisting of Π 1 1 sets. In particular, it is completely nonmeasurable with respect to Lebesgue measure and Baire category.…”
Section: Earlier Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is easy to check (see similar arguments in [5]) that every Bernstein set is completely nonmeasurable with respect to every σ -ideal with a base consisting of Π 1 1 sets. In particular, it is completely nonmeasurable with respect to Lebesgue measure and Baire category.…”
Section: Earlier Resultsmentioning
confidence: 95%
“…Moreover, if is an algebra of subsets of R, having the property that every set which is in , but not in the hereditary ideal of , contains a perfect set, then no Bernstein set can be a member of . Most natural algebras of subsets of R have this property (see [5]), therefore Bernstein sets are in a sense universal examples of nonmeasurable sets. In our paper, we introduce a general method of constructing Bernstein sets having additional algebraic properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, related results for other σ-ideals were obtained by Kharazishvili [10] and by Cichoń and Jasiński [5]. In another direction, Ciesielski, Fejzić and Freiling [6] proved among others, that for every set C ⊆ R, there exists a set A ⊂ C such that λ * (A + A) = 0 and λ * (A + A) = λ * (C + C), where λ * and λ * denote the inner and the outer Lebesgue measure respectively (but for simpler proof see the work by Marcin Kysiak [13]). It is also worth to mention the famous Erdös-Kunen-Mauldin theorem [9].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…see the work by Marcin Kysiak [13]). It is also worth to mention the famous Erdös-Kunen-Mauldin theorem [9].…”
mentioning
confidence: 98%
“…Recall that the algebraic sums of Borel sets were already considered by Erdős and Stone [11] and Rogers [25], where the authors showed that there are two Borel sets A B ⊂ R such that A + B is not Borel, see also [3] for another example. Moreover, recently it was shown that there is an uncountable Borel set B ⊂ R such that C + D is Borel for all Borel sets C D ⊂ B [18].…”
Section: Let X and Y Be Polish Spacesmentioning
confidence: 99%